Who's afraid of institutionalizing health technology assessment (HTA)?: Interests and policy positions on HTA in the Czech Republic - Löblová, Olga (Health economics, policy, and law, 2018)
This article identifies the interests and policy positions of key health policy stakeholders regarding the creation of a health technology assessment (HTA) agency in the Czech Republic, and what considerations influenced them. Vested interests have been suggested as a factor mitigating the diffusion of HTA bodies internationally. The Czech Republic recently considered and discarded establishing an HTA agency, making it a good case for studying actors' policy positions throughout the policy debates. Findings are based on in-depth, semi-structured expert and elite interviews with 34 key Czech health policy actors, supported by document analysis and extensive triangulation. Findings show that the HTA epistemic community of 'aspiring agents' was the only actor strongly in favor of an HTA body. Payers and the medical device and diagnostics industry were against it; patients and clinicians had no clear preferences. Original decision-makers were in favor but a new minister of health opted for a simpler policy alternative to solve his need for expertise. Existing institutions, policy alternatives and the institutional design of a future HTA body influence domestic actors' preferences for or against an HTA agency. Domestic and international proponents of HTA should give serious thought to their concerns when advocating for HTA bodies.
Keywords: rozhodování organizační; Interviews as Topic; Health Policy; Decision Making, Organizational; Humans; Česká republika; lidé; rozhovory jako téma; hodnocení biomedicínských technologií; zdravotní politika; Technology Assessment, Biomedical; Czech Republic